Design of information management system for structural monitoring based on network fragmentation. Issue 4 (18th April 2020) - Yue, Guoning
Aiming at the shortcomings of current information management system, such as low security, poor economy and long response time, a design method of structure monitoring information management system based on network fragments is proposed. Firstly, the overall architecture of the network debris structure monitoring information management system is designed and the requirements of the monitoring information management system are analysed. Then, based on the analysis of the main characteristics of the network debris monitoring information management system, the modules and subsystems of the system are designed separately, and the system data management scheme is given. In this way, the design of structured monitoring information management system based on network fragments is completed. The experimental results show that the information management system can manage the network information safely and economically. The response time is short, and the overall performance of the structured monitoring information management system is improved.